Towards an automated pipeline to model a complex-network-driven analysis of microRNAs in cancer: a TCGA-BRCA case study - Roberta, Mylena; Geraldo, Murilo Vieira; Santanchè, André (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
We present the Transparent Reproducible Pipeline (TRP), a core component of our framework for systematizing the comparative analysis of cancer microRNA networks. The TRP is an open, stepwise pipeline for modeling these networks. It provides transparency in materializing intermediary artifacts as tables with schemas, affording explicit semantics and annotation-based provenance. It also offers reproducibility through its open-source code and comprehensive documentation, all accessible without restrictions. To apply and validate the TRP, we conducted a controlled study on breast cancer based on the Breast Invasive Carcinoma (BRCA) project of The Cancer Genome Atlas (TCGA), achieving promising results.